Comparison of semiconductor lasers at wavelength 980 nm & 1480 nm using InGaAs for EDFA pumping scheme - Satyo Pradana; Ary Syahriar; Sasono Rahardjo; Ahmad H. Lubis (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Long distance Optical Communications are affected by many problems; loss of signal is one of them. Erbium Doped Fiber Amplifier (EDFA) is the key to solve it. By using Semiconductor Laser as pumping source for EDFA, the signal can brought back the performed of EDFA into normal condition. EDFA has a good wavelength operation at 980nm & 1480nm, in that case Semiconductor Laser using InGaAs at 980nm & 1480nm is suitable for them. By using selected wavelength and materials, the Semiconductor Laser can be produced properly. Also, determining the parameter is the important things to construct the Laser. By using Rate Equation, the performed of Semiconductor Laser can obtained several result. Those are injection current as a function of voltage, carrier density, photon density and output power as a function of injection current.